تطور نشاط سوق الأوراق المالية الإسلامية: دراسة حالة الكويت - حفيظ، عبدالحميد; براهمى، زرزور; بهلول، لطيفة (الهيئة العالمية للتسويق الإسلامي, 2019)
The importance of the Islamic securities market stems from the role it plays in the process of growth and economic development. The interest transactions in this market positively affect the results of this growth and development. The basis of the Islamic securities market is dealing with equities and Islamic sukuk compliant instruments. The study dealt with the development of the activity of the stock market in Kuwait through an analytical presentation of the most important indicators of this market. The study concluded that the Kuwait experience is successful in dealing with the stock market, as it played a financing role, especially that investors prefer at the level of this market to deal and invest in securities of companies operating in accordance with the provisions of Islamic law, especially oil and gas companies and telecommunications companies and banking companies, the client seeks to create investment tools Halal compliant with the principles of Islamic law, which is supposed to be the case in all Islamic societies so that this market plays its role effectively and comprehensively.
تنبع اهمية سوق الاوراق المالية الاسلامية من الدور الذي تلعبه في عملية النمو والتطور الاقتصادي، كما أن التعاملات غير الربوية في هذه السوق تؤثر ايجابيا على نتائج هذا النمو والتطور، إن أساس السوق أوراق المالية الاسلامية هو التعامل بالأسهم والصكوك الإسلامية المتوافقة مع الشريعة الإسلامية؛ تناولت الدراسة مدى تطور نشاط سوق الاوراق المالية في الكويت من خلال عرض تحليلي لأهم مؤشرات هذه السوق. خلصت الدراسة إلا أن التجربة الكويتية تعد ناجحة في التعامل بسوق الأوراق المالية، إذ أنها لعبت دورا تمويليا خاصة أن المستثمرين يفضلون على مستوى هذه السوق التعامل والاستثمار في الأوراق المالية للشركات التي تعمل وفق أحكام الشريعة الإسلامية، وخاصة منها شركات قطاع النفط والغاز وشركات قطاع الاتصالات وشركات قطاع البنوك، أي أن المتعامل يسعى لخلق أدوات استثمارية خلال تتوافق مع مبادئ الشريعة الإسلامية وهو ما يفترض أن يكون عليه الحال في جميع المجتمعات الإسلامية حتى تؤدي هذه السوق دورها بشكل فعال وشامل والمتمثل أساسا في جمع الفوائض وتوجهها إلى أصحاب العجز.
Keywords: الأسواق المالية -- المصارف الإسلامية -- الصكوك الإسلامية -- الأنشطة الاقتصادية -- الكويت